Secondary battery and electronic device

By controlling the mass content of silicon elements and the components of the electrolyte, using a double-layer coating structure and a specific thickness range, the poor wetting and volume expansion of silicon-based anode materials in lithium-ion batteries are solved, and the battery performance and safety enhancement are achieved.

CN119905644APending Publication Date: 2025-04-29NINGDE AMPEREX TECHNOLOGY LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510399993.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The poor wetting properties of the silicon-based negative electrode material in lithium-ion batteries lead to a decline in battery performance and volume expansion during charging and discharging, reducing cycle life and safety.

Method used

By controlling the mass content of silicon elements in the first and second material layers, as well as the components and content of the electrolyte, a double-layer coating structure and a specific thickness range are adopted, combined with the use of the compound of formula I of the electrolyte, the wetting property of the electrolyte is improved and the volume expansion of the secondary battery is reduced.

Benefits of technology

While maintaining high energy density, it effectively reduces the volume expansion of the battery during charging and discharging, extends the cycle life of the battery, and improves its safety and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_19
    Figure SMS_19
  • Figure SMS_37
    Figure SMS_37
Patent Text Reader

Abstract

The invention provides a secondary battery and an electronic device, and belongs to the technical field of energy storage. The secondary battery comprises a negative pole piece and an electrolyte, the negative pole piece comprises a negative pole material layer; the negative electrode material layer comprises a first material layer and a second material layer; the first material layer is arranged between the negative electrode current collector and the second material layer; based on the total mass of the first material layer, the mass content of the silicon element in the first material layer is x%; based on the total mass of the second material layer, the mass content of the silicon element in the second material layer is y%; 0 < = x < = 35, 3.5 < = y < = 70, and x < = y; the electrolyte comprises a compound shown in the formula I, the mass content of the compound shown in the formula I is A% based on the total mass of the electrolyte, and A is larger than or equal to 1 and smaller than or equal to 30. By controlling the mass content of the silicon element in the first material layer and the second material layer and the components and content of the electrolyte, the wettability of the electrolyte can be improved, and the volume expansion of the secondary battery is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of energy storage technology, and specifically relates to a secondary battery and an electronic device. Background Art

[0002] As a rechargeable energy storage device, secondary batteries can store and release electrical energy through electrochemical reactions. They are an indispensable key component of electronic devices, electric vehicles and energy storage systems. With the continuous iteration and upgrading of technology, lithium-ion batteries are widely used due to their high energy density, long cycle life and environmental friendliness.

[0003] In the development of lithium-ion batteries, the selection of electrode materials is crucial. At present, graphite is one of the most commonly used negative electrode materials, with good conductivity and stability. However, as the demand for energy storage evolves towards high energy density, silicon-based materials with higher theoretical specific capacity have gradually become the focus of research. However, the wettability of silicon-based materials is poor, which will affect the performance of the battery; and the volume of the silicon-based negative electrode changes greatly during the charging and discharging process, which is prone to volume expansion and damage to the material structure, which not only reduces the cycle life of the battery, but also may cause safety hazards such as internal short circuits in the battery. Therefore, improving the wettability of the electrolyte and reducing the volume expansion of secondary batteries have become an important direction for current technological development. Summary of the invention

[0004] In view of this, the present application provides a secondary battery and an electronic device, which improves the wettability of the electrolyte and reduces the volume expansion of the secondary battery by controlling the mass content of the silicon element in the first material layer and the second material layer and the composition and content of the electrolyte.

[0005] In a first aspect, the present application provides a secondary battery, comprising a negative electrode plate and an electrolyte; the negative electrode plate comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector; wherein the negative electrode material layer comprises a first material layer and a second material layer; the first material layer is disposed between the negative electrode current collector and the second material layer; based on the total mass of the first material layer, the mass content of silicon in the first material layer is x%; based on the total mass of the second material layer, the mass content of silicon in the second material layer is y%; 0≤x≤35, 3.5≤y≤70, and x≤y; The electrolyte comprises a compound of formula I:

[0006] Formula I Wherein, R1, R2, R3, R4, R5, and R6 are independently selected from fluorine atoms, C1-C3 alkyl groups, and fluorine-substituted C1-C3 alkyl groups; based on the total mass of the electrolyte, the mass content of the compound of formula I is A%, 1≤A≤30. The negative electrode plate of the present application adopts double-layer coating, and by controlling the mass content of silicon elements in the first material layer and the second material layer, and controlling the composition and content of the electrolyte, the wettability can be improved, so that the secondary battery can maintain a high energy density while effectively reducing the volume expansion during the charge and discharge process, thereby extending the cycle life of the battery and improving its safety and reliability.

[0007] In some embodiments, the secondary battery satisfies at least one of the following characteristics: (1) 0≤x≤21; (2) 10.5≤y≤70. When the mass content of silicon in the first material layer and the second material layer meets the above range, wettability can be further improved and volume expansion of the secondary battery can be reduced.

[0008] In some embodiments, 2≤A≤20. The mass content of the compound of formula I in the electrolyte is adjusted to meet the above range, so that it can better cooperate with other components of the electrolyte, further improve wettability, and reduce volume expansion of the secondary battery.

[0009] In some embodiments, the thickness of the first material layer is a μm, the thickness of the second material layer is b μm, 15≤a≤100, 5≤b≤70. When the thickness of the first material layer and the second material layer meet the above ranges, wettability can be further improved and volume expansion of the secondary battery can be reduced.

[0010] In some embodiments, the compound of formula I comprises at least one of the following compounds: Formula I-1, Formula I-2, Formula I-3, Formula I-4, Formula I-5, Formula I-6, Formula I-7, Formula I-8, Formula I-9, Formula I-10, Formula I-11, Formula I-12, Formula I-13, Formula I-14, Formula I-15, Formula I-16, Formula I-17.

[0011] The compound of formula I of the present application is combined with the electrolyte system to further improve the wettability of the electrolyte and reduce the volume expansion of the secondary battery.

[0012] In some embodiments, the secondary battery includes a shell and an electrode assembly; the shell is made of steel or aluminum, and the volume of the secondary battery is 2 cm 3 ~150 cm 3 When the volume range of the secondary battery meets the above range, the wettability can be further improved and the volume expansion of the secondary battery can be reduced.

[0013] In some embodiments, the secondary battery further comprises a positive electrode plate, the positive electrode plate comprises a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector; the positive electrode material layer comprises a positive electrode active material; the positive electrode active material is lithium cobalt oxide, and the lithium cobalt oxide comprises a doping element; the doping element comprises at least one of Mg element, Ti element, Zr element, Nb element, Y element, Cr element, V element, Ge element, Mo element, Sr element, and Al element, and the doping element mass accounts for 0.1% to 1% based on the mass of the lithium cobalt oxide. The doping elements in the lithium cobalt oxide of the present application can enhance the thermal stability of the material, increase the cycle life, and improve the overall performance of the secondary battery.

[0014] In some embodiments, the volume of the secondary battery is 4 cm 3 ~120 cm 3 By controlling the volume of the secondary battery, the wettability can be further improved and the volume expansion of the secondary battery can be reduced.

[0015] In some embodiments, the electrolyte further includes an additive, the additive including at least one of succinonitrile, adiponitrile, 1,3,6-hexanetrinitrile, 1,2,3-tri(2-cyano)propane, ethylene glycol (bispropionitrile) ether, trans-butylene dinitrile, 1,3-propane sultone, and 1,4-butane sultone; based on the total mass of the electrolyte, the mass content of the additive is B%, 0.6≤B≤8. The present application uses additives in combination with the above electrolyte system to improve the stability of the CEI membrane (positive electrode electrolyte interface membrane), thereby further improving the wettability and reducing the volume expansion of the secondary battery.

[0016] In a second aspect, the present application provides an electronic device comprising any of the above-mentioned secondary batteries. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0018] In order to solve the problems of the prior art, the present application provides a secondary battery in a first aspect, including a negative electrode plate and an electrolyte; the negative electrode plate includes a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector; wherein the negative electrode material layer includes a first material layer and a second material layer; the first material layer is arranged between the negative electrode current collector and the second material layer; based on the total mass of the first material layer, the mass content of silicon in the first material layer is x%; based on the total mass of the second material layer, the mass content of silicon in the second material layer is y%; 0≤x≤35, 3.5≤y≤70, and x≤y; The electrolyte comprises a compound of formula I:

[0019] Formula I Wherein, R1, R2, R3, R4, R5, and R6 are independently selected from fluorine atoms, C1-C3 alkyl groups, and fluorine-substituted C1-C3 alkyl groups; based on the total mass of the electrolyte, the mass content of the compound of formula I is A%, 1≤A≤30. The inventors found that: the wettability of silicon-based materials is poor, and the use of a double-layer coating method to control the ratio of inner / outer silicon elements within a specific range, while using the compound of formula I, can not only ensure the energy density of the battery, but also facilitate the rapid penetration of the electrolyte into all pole pieces. When the electrolyte in the middle of the battery is almost exhausted during the cycle, the electrolyte at the edge of the battery can be replenished in time, reducing the probability of local interface problems in the battery and reducing the expansion of the battery.

[0020] In some embodiments, 0≤x≤35, preferably 0≤x≤21, for example, x can be 0, 2, 3, 7, 9, 11, 14, 18, 21, 24, 26, 28, 32, 34, 35 or a value in the range formed by any two of these values. The present application regulates the mass content of silicon in the first material layer to meet the above range, so that the silicon content of the inner layer is within a suitable range, thereby further improving wettability and reducing volume expansion of the secondary battery.

[0021] In some embodiments, 3.5≤y≤70, preferably 10.5≤y≤70, for example, y can be 3.5, 6, 10.5, 16, 24, 26, 31, 36, 44, 47, 54, 57, 60, 68, 70 or a value in the range formed by any two of these values. The present application regulates the mass content of silicon in the second material layer to meet the above range, so that the silicon content of the outer layer is within a suitable range, thereby further improving wettability and reducing volume expansion of the secondary battery.

[0022] In some embodiments, 1≤A≤30, preferably 2≤A≤20, for example, the value of A can be 1, 2, 5, 7, 9, 11, 14, 15, 17, 20, 22, 25, 27, 28, 30 or a value in the range formed by any two of these values. The mass content of the compound of formula I is regulated in the present application to meet the above range, which is conducive to the coordination with other components of the electrolyte, thereby further improving the wettability and reducing the volume expansion of the secondary battery.

[0023] In some embodiments, the thickness of the first material layer is a μm, the thickness of the second material layer is b μm, 15≤a≤100, 5≤b≤70. The present application regulates the thickness of the first material layer and the second material layer to ensure that the battery has a certain energy density while allowing the electrolyte to have good permeability in the electrode, thereby further improving the wettability and reducing the volume expansion of the secondary battery.

[0024] In some embodiments, 15≤a≤100, preferably 30≤a≤90, for example, a can be 15, 17, 26, 30, 35, 43, 51, 58, 62, 70, 78, 82, 90, 97, 100 or a value in a range formed by any two of these values. The present application regulates the thickness of the first material layer so that the electrolyte can quickly penetrate the first material layer, thereby further improving the wettability and reducing the volume expansion of the secondary battery.

[0025] In some embodiments, 5≤b≤70, preferably 10≤b≤60, for example, b can be 5, 7, 10, 16, 20, 25, 32, 37, 43, 49, 53, 60, 65, 68, 70 or a value within a range formed by any two of these values. The present application regulates the thickness of the second material layer so that the electrolyte can quickly penetrate the second material layer and reach the first material layer, thereby further improving the wettability and reducing the volume expansion of the secondary battery.

[0026] In some embodiments, the compound of formula I comprises at least one of the following compounds: Formula I-1, Formula I-2, Formula I-3, Formula I-4, Formula I-5, Formula I-6, Formula I-7, Formula I-8, Formula I-9, Formula I-10, Formula I-11, Formula I-12, Formula I-13, Formula I-14, Formula I-15, Formula I-16, Formula I-17.

[0027] In the electrolyte system of the present application, the compound of formula I can form a suitable adsorption film in the organic solution, reduce the surface tension of the electrolyte, thereby further improving the wettability and reducing the volume expansion of the secondary battery.

[0028] In some embodiments, the secondary battery includes a shell and an electrode assembly; the shell is made of steel or aluminum, and the volume of the secondary battery is 2 cm 3 ~150 cm 3 , preferably 4 cm 3 ~120 cm 3 For example, the volume value of the secondary battery can be 2, 4, 24, 32, 38, 52, 64, 80, 83, 96, 109, 120, 138, 143, 150 or a value in the range formed by any two of these values. The present application regulates the volume of the secondary battery, can control the length, width and thickness of the battery within a certain range, limit the transmission distance of the electrolyte, thereby further improving the wettability and reducing the volume expansion of the secondary battery.

[0029] In some embodiments, the secondary battery further comprises a positive electrode plate, the positive electrode plate comprises a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector; the positive electrode material layer comprises a positive electrode active material; the positive electrode active material is lithium cobalt oxide, and the lithium cobalt oxide comprises a doping element; the doping element comprises at least one of Mg element, Ti element, Zr element, Nb element, Y element, Cr element, V element, Ge element, Mo element, Sr element, and Al element, and based on the mass of the lithium cobalt oxide, the mass proportion of the doping element is 0.1% to 1%, preferably 0.2% to 0.8%, for example, the mass proportion of the doping element can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a value within the range of any two of these values. The present application regulates the mass proportion of the doping element in the positive electrode active material, which can enhance the thermal stability of the material, increase the cycle life, and improve the overall performance of the secondary battery.

[0030] In some embodiments, the electrolyte further includes an additive, the additive including at least one of succinonitrile, adiponitrile, 1,3,6-hexanetrinitrile, 1,2,3-tri(2-cyano)propane, ethylene glycol (bispropionitrile) ether, trans-butylene dinitrile, 1,3-propane sultone, and 1,4-butane sultone; based on the total mass of the electrolyte, the mass content of the additive is B%, 0.6≤B≤8, preferably 1.1≤B≤7.0, for example, the value of B can be 0.6, 1.1, 1.5, 1.9, 2.4, 3.2, 3.8, 4.3, 5.0, 5.5, 6.0, 6.8, 7.0, 7.9, 8 or a value within the range of any two of these values. The present application uses additives in combination with the above-mentioned electrolyte system to form a stable positive electrode electrolyte interface (CEI) film at the electrode interface, thereby further reducing the volume expansion of the secondary battery.

[0031] In the present application, the electrolyte also includes lithium salts and non-aqueous solvents. The lithium salt may include, but is not limited to, at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalate borate) LiB(C2O4)2 (LiBOB), lithium difluorooxalate borate LiBF2(C2O4) (LiDFOB), LiNO3, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiC(SO2CF3)3, and Li2SiF6. The present application does not limit the content of lithium salts in the electrolyte, as long as the purpose of the present application can be achieved. The present application has no special restrictions on non-aqueous solvents, as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include, but is not limited to, at least one of ether compounds or other organic solvents. The above-mentioned ether compound may include but is not limited to at least one of 1,3-dioxolane (DOL), ethylene glycol dimethyl ether (1,2-dimethoxyethane, DME), dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran.

[0032] The present application does not particularly limit the types of other organic solvents, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of ether compounds, dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate or other organic solvents. The above-mentioned ether compounds may include but are not limited to at least one of ethylene glycol dimethyl ether, dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran.

[0033] The present application does not particularly limit the type of secondary battery, which may include any device that generates an electrochemical reaction. In the present application, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery (lithium ion polymer battery), etc.

[0034] The secondary battery of the present application includes a negative electrode plate and an electrolyte; the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector; the negative electrode material layer includes a first material layer and a second material layer; the first material layer is disposed between the negative electrode current collector and the second material layer; the electrolyte is selected from any of the above electrolytes. During the charge and discharge cycle of the secondary battery, the electrolyte reacts on the surface of the negative electrode material layer to form a solid electrolyte interface film (SEI film).

[0035] The above-mentioned “negative electrode material layer disposed on at least one surface of the negative electrode current collector” means that the negative electrode material layer can be located on one surface of the negative electrode current collector along its thickness direction, or on two surfaces of the negative electrode current collector along its thickness direction. It should be noted that the “surface” here can be the entire area of ​​the surface of the negative electrode current collector, or a partial area of ​​the surface of the negative electrode current collector. This application is not particularly limited, as long as the purpose of this application can be achieved.

[0036] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or composite current collector (such as carbon copper composite current collector, nickel copper composite current collector, titanium copper composite current collector, etc.).

[0037] The negative electrode material layer of the present application includes a negative electrode active material, and the negative electrode active material may include but is not limited to graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composites, SiO x(0.5<x<1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate TiO2-Li4Ti5O 12 , at least one of Li-Al alloy and metallic lithium.

[0038] The negative electrode material layer in the present application may also include a negative electrode binder and a negative electrode conductor, or the negative electrode material layer may also include a negative electrode binder, a negative electrode conductor and a thickener. The present application does not particularly limit the type of negative electrode binder in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the negative electrode binder may include but is not limited to at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyolefins, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, modified polyvinylidene fluoride, modified styrene-butadiene rubber (SBR) or polyurethane. In some embodiments, the polyolefin binder includes at least one of polyethylene, polypropylene, polyolefin ester, polyolefin alcohol or polyacrylic acid. The present application does not particularly limit the type of negative electrode conductor in the negative electrode material layer, as long as the purpose of the present application can be achieved. In some embodiments, the negative electrode conductor includes carbon-based materials, such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black or carbon fiber; metal-based materials, such as metal powder or metal fiber of copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives; or mixtures thereof. The present application does not particularly limit the type of thickener, as long as the purpose of the present application can be achieved. For example, the thickener may include but is not limited to at least one of sodium carboxymethyl cellulose or carboxymethyl cellulose. The present application does not particularly limit the mass ratio of the negative electrode active material, the negative electrode conductive agent, the negative electrode binder, and the thickener in the negative electrode material layer. Those skilled in the art can select according to actual needs, as long as the purpose of the present application can be achieved.

[0039] In the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode current collector" means that the positive electrode material layer can be located on one surface of the positive electrode current collector along its own thickness direction, or on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the positive electrode current collector, or it can be a partial area of ​​the surface of the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.

[0040] The present application has no particular restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the positive electrode current collector may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector). The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate.

[0041] The positive electrode material layer of the present application includes a positive electrode active material. The present application has no particular restrictions on the type of the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include lithium nickel cobalt manganese oxide (LiNi 0.90 Co 0.05 Mn 0.05 O2 (NCM955), NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, spinel lithium manganese oxide, spinel lithium nickel manganese oxide and at least one of lithium titanate.

[0042] In the present application, there is no particular limitation on the thickness of the positive electrode current collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, and the thickness of the single-sided positive electrode material layer is 30 μm to 120 μm.

[0043] In the present application, the positive electrode material layer may further include a positive electrode binder and a positive electrode conductor. The present application does not particularly limit the type of positive electrode binder in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the positive electrode binder may include but is not limited to polyvinylidene fluoride, polytetrafluoroethylene, polyolefins, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, modified polyvinylidene fluoride, modified styrene-butadiene rubber (SBR) or at least one of polyurethane. In some embodiments, the polyolefin binder includes at least one of polyethylene, polypropylene, polyolefin ester, polyolefin alcohol or polyacrylic acid.

[0044] The present application has no particular restrictions on the type of positive electrode conductive agent in the positive electrode material layer, as long as the purpose of the present application can be achieved. In some embodiments, the positive electrode conductive agent includes carbon-based materials, such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black or carbon fiber; metal-based materials, such as metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives; or mixtures thereof. The present application has no particular restrictions on the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder in the positive electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, the loading amount of the positive electrode active material in the positive electrode sheet is 4.0 mg / cm 2 Up to 10.0 mg / cm 2 .

[0045] In order to prevent short circuit, a separator is usually provided between the positive electrode and the negative electrode of the secondary battery. In this case, the electrolyte of the present application is usually used after being infiltrated into the separator.

[0046] There is no particular restriction on the material and shape of the isolation membrane, as long as the effect of the present application is not significantly impaired. The isolation membrane may be a resin, glass fiber, inorganic substance, etc. formed of a material that is stable to the electrolyte of the present application. In some embodiments, the isolation membrane includes a porous sheet or a non-woven fabric-like material with excellent liquid retention. Examples of materials for resin or glass fiber isolation membranes may include, but are not limited to, polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, etc. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above isolation membranes may be used alone or in any combination.

[0047] The separator may also be a material formed by laminating the above materials, examples of which include, but are not limited to, a three-layer separator formed by laminating polypropylene, polyethylene, and polypropylene in this order.

[0048] Examples of inorganic materials may include, but are not limited to, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates (eg, barium sulfate, calcium sulfate, etc.). The form of the inorganic material may include, but is not limited to, granular or fibrous.

[0049] The separator may be in the form of a thin film, examples of which include, but are not limited to, nonwoven fabrics, woven fabrics, microporous films, etc. In the thin film form, the separator has a pore size of 0.01 μm to 1 μm and a thickness of 5 μm to 50 μm. In addition to the above-mentioned independent thin film separators, the following separators can also be used: a separator formed by forming a composite porous layer containing the above-mentioned inorganic particles on the surface of the positive electrode and / or the negative electrode using a resin-based adhesive, for example, a separator formed by using a fluororesin as an adhesive to form a porous layer on both sides of the positive electrode with alumina particles having a particle size of 90% less than 1 μm.

[0050] The thickness of the separator is arbitrary. In some embodiments, the thickness of the separator is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the separator is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the separator is within the above range, insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the secondary battery can be ensured.

[0051] The secondary battery of the present application also includes a packaging bag for containing a positive electrode, a negative electrode, a separator and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.

[0052] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and the present application has no special restrictions. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery; or stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the packaging bag as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.

[0053] In a second aspect, the present application provides an electronic device comprising any of the above-mentioned secondary batteries.

[0054] In some embodiments, the electronic devices of the present application include, but are not limited to laptop computers, pen-type computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.

[0055] The scheme of the present application is described below by taking lithium-ion batteries as an example in combination with the following specific embodiments. Unless otherwise specified, the raw materials used in the following embodiments are all from ordinary commercial products, and the devices or equipment used are all purchased from conventional market sales channels. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0056] Test Method Wetting effect test: After the injection, the lithium-ion battery was placed in a 0°C environment. After standing for different periods of time, the lithium-ion battery was disassembled to confirm the time it took for the electrolyte to completely soak all the pole pieces and the separator. The soaking time was calculated in hours. The shorter the time, the better the soaking effect of the electrolyte: 0 hours < immersion time ≤ 1 hour, recorded as 1 hour; If the immersion time is 1 hour < ≤ 2 hours, it will be recorded as 2 hours; 2 hours < immersion time ≤ 3 hours, recorded as 3 hours; 3 hours < immersion time ≤ 4 hours, recorded as 4 hours; 4 hours < immersion time ≤ 5 hours, recorded as 5 hours; 5 hours < immersion time ≤ 6 hours, recorded as 6 hours; 6 hours < immersion time ≤ 7 hours, recorded as 7 hours; 7 hours < immersion time ≤ 8 hours, recorded as 8 hours; 8 hours < immersion time ≤ 9 hours, recorded as 9 hours; 9 hours < immersion time ≤ 10 hours, recorded as 10 hours; 10 hours < immersion time ≤ 11 hours, recorded as 11 hours; 11 hours < immersion time ≤ 12 hours, recorded as 12 hours; 12 hours < infiltration time, recorded as 13 hours.

[0057] Thickness expansion test: Place the lithium-ion battery in a 0℃ constant temperature environment and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature state of 0℃. Charge to 3.95V at a constant current of 0.5C, place the lithium-ion battery in a 25℃ environment for 4 hours, and test the initial thickness of the lithium-ion battery at this time h1. Place the lithium-ion battery in a 0℃ constant temperature environment again and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature state of 0℃. Charge to 4.5V at a constant current of 0.5C, charge at a constant voltage until the current is 0.025C, let it stand for 5 minutes, and discharge to 3.0V at a constant current of 0.5C. Cycle the above charge and discharge steps for 200 times, place the lithium-ion battery in a 25℃ environment for 4 hours, and test the thickness of the lithium-ion battery at this time h2; Thickness expansion rate = (h2-h1) / h1×100%.

[0058] High temperature storage flatulence test: Place the lithium-ion battery in a 25℃ constant temperature environment and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature of 25℃. Charge it to 3.95V at a constant current of 0.5C, and test the initial thickness of the lithium-ion battery at this time, which is H1. Charge it to 4.5V at a constant current of 0.5C, charge it to a current of 0.025C at a constant voltage, and let it stand for 5 minutes. Then, store the lithium-ion battery in a high temperature box at 80℃ for 12 hours. After taking it out, immediately test the thickness of the lithium-ion battery at this time, which is H2. High temperature storage inflation rate = (H2-H1) / H1×100%.

[0059] 45℃ Cycle Capacity Retention Test: Place the lithium-ion battery in a 45°C constant temperature environment and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature of 45°C. Charge to 4.5V at a constant current of 0.5C, charge to a current of 0.025C at a constant voltage, let it stand for 5 minutes, and discharge to 3.0V at a constant current of 0.5C. Repeat the above charge and discharge steps for 200 cycles, and record the first discharge capacity m1 and the last discharge capacity m2; 45℃ cycle capacity retention rate = m2 / m1×100%.

[0060] Silicon element mass content test: Test for silicon content in the first material layer: Scrape the active material layer powder sample in an area 10μm thick from the surface of the negative electrode sheet along the thickness direction of the negative electrode sheet, and measure the silicon content in the active material layer by inductively coupled plasma spectrometer (ICP).

[0061] Test of silicon content in the second material layer: Scrape the active material layer powder sample in an area 10 μm thick from the negative electrode current collector, and measure the silicon content in the active material layer by ICP.

[0062] Secondary battery volume test: Prepare a container and fill it with an appropriate amount of water. Measure the volume of the water in the container, record it as V1, and immerse the battery completely in the liquid. Measure the total volume of the water and the battery at this time, record it as V2. The volume of the battery = V2-V1.

[0063] Example 1-1 <Preparation of Electrolyte> In a dry argon atmosphere glove box, lithium hexafluorophosphate (LiPF6) as a supporting electrolyte is dissolved in a solution containing diethyl carbonate and a compound of formula I. Based on the mass of the electrolyte, the mass content of lithium hexafluorophosphate is 10%, the mass content of the compound of formula I is shown in Table 1 below, and the remainder is diethyl carbonate. Among them, the compound of formula I is I-1.

[0064] <Preparation of negative electrode sheet> Graphite material, silicon-carbon material, conductive agent carbon black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are added to deionized water solvent in a mass ratio of 46:50:1.5:1.5:1, and stirred and mixed thoroughly to form a uniform first negative electrode slurry. Graphite material, silicon-carbon material, conductive agent carbon black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are added to deionized water solvent in a mass ratio of 26:70:1.5:1.5:1, and stirred and mixed thoroughly to form a uniform second negative electrode slurry; wherein the silicon-carbon material includes porous carbon and nano-silicon located in the pores of the porous carbon, and the mass proportion of silicon in the silicon-carbon material is 50%.

[0065] The first negative electrode slurry is coated on both sides of the negative electrode current collector copper foil, dried and cold pressed to form a first material layer; the second negative electrode slurry is coated on the first material layer, dried and cold pressed to form a second material layer, and then cut into pieces and welded to the pole ears to obtain a negative electrode of appropriate size.

[0066] The negative electrode material layer includes a first material layer and a second material layer; the first material layer is arranged between the negative electrode current collector and the second material layer; based on the total mass of the first material layer, the mass content of silicon element in the first material layer is x%; based on the total mass of the second material layer, the mass content of silicon element in the second material layer is y%; the thickness of the first material layer is a μm, a is 12, and the thickness of the second material layer is b μm, b is 72.

[0067] The mass content of silicon in the first material layer and the second material layer, and the thickness of the first material layer and the second material layer are shown in Table 1 below.

[0068] <Preparation of positive electrode sheet> The positive electrode active material lithium cobalt oxide, the positive electrode binder polyvinylidene fluoride (PVDF), and the positive electrode conductive agent Super P are mixed in a mass ratio of 97:1.6:1.4, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75wt%, and stir evenly. Among them, the lithium cobalt oxide includes the doping element Mg element, and the mass proportion of the doping element is 0.1% based on the mass of the lithium cobalt oxide. The positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil with a thickness of 10μm, dried, and cold pressed to obtain the positive electrode sheet.

[0069] <Diaphragm> A polyethylene-polypropylene composite film with a thickness of 7 μm was used.

[0070] <Preparation of lithium-ion batteries> The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, so that the separator is located between the positive electrode sheet and the negative electrode sheet to play a barrier role, and then stacked in order and fixed to obtain an electrode assembly with a laminated structure. The lithium-ion battery also includes a shell, which is made of steel shell. The volume of the secondary battery is 160 cm 3 The electrode assembly obtained above is placed in a shell, placed in a vacuum oven at 85°C for 12 hours to remove moisture, injected with the prepared electrolyte, and a lithium-ion battery is obtained through vacuum packaging, standing, and formation processes.

[0071] The main difference between the embodiments and comparative examples in Table 1 and Embodiment 1-1 is that the parameters shown in Table 1 are adjusted.

[0072] Table 1

[0073] As can be seen from Table 1, the present application can improve wettability and reduce the volume expansion of the secondary battery by controlling the mass content of the compound of formula I in the electrolyte to satisfy 1≤A≤30, and the mass content of silicon in the first material layer and the mass content of silicon in the second material layer to satisfy 0≤x≤35, 3.5≤y≤70, and x≤y. In particular, when the mass content of the compound of formula I in the electrolyte is regulated to satisfy 2≤A≤20, the wettability can be further improved and the volume expansion of the secondary battery can be reduced. Moreover, when the mass content of silicon in the first material layer and the mass content of silicon in the second material layer are regulated to satisfy 0≤x≤21, 10.5≤y≤70, the wettability can be further improved and the volume expansion of the secondary battery can be reduced.

[0074] The main difference between each embodiment in Table 2 and embodiments 1-6 is the thickness of the first material layer and the second material layer. The thickness of the first material layer and the second material layer are shown in Table 2.

[0075] Table 2

[0076] As can be seen from Table 2, the present application can further improve wettability and reduce volume expansion of the secondary battery by adjusting the thickness of the first material layer and the thickness of the second material layer to satisfy 15≤a≤100 and 5≤b≤70.

[0077] The main difference between each embodiment in Table 3 and embodiments 2-6 is the volume of the secondary battery. The volume of the secondary battery of each embodiment is shown in Table 3.

[0078] Table 3

[0079] As shown in Table 3, the present invention controls the volume of the secondary battery to 2 cm 3 ~150 cm 3 , which can further improve wettability and reduce the volume expansion of secondary batteries.

[0080] The main difference between each embodiment in Table 4 and Embodiment 3-3 is that the doping elements and the mass ratio of the doping elements in the lithium cobalt oxide are adjusted. The specific adjustment parameters and performance test results are shown in Table 4.

[0081] Table 4

[0082] As can be seen from Table 4, the present application can reduce high-temperature storage flatulence, enhance the thermal stability of the material, increase the cycle life, and improve the overall performance of the secondary battery by controlling the mass ratio of the doping elements in the lithium cobalt oxide.

[0083] In particular, when the mass proportion of the doping elements is adjusted to meet 0.2%~0.8%, the thermal stability of the material can be further enhanced.

[0084] The main difference between each embodiment in Table 5 and embodiment 4-3 is that the electrolyte is prepared according to a method comprising the following steps: In a dry argon atmosphere glove box, the additive was dissolved in a solution containing lithium hexafluorophosphate, diethyl carbonate and the compound of formula I. Based on the mass of the electrolyte, the mass contents of lithium hexafluorophosphate and the compound of formula I were the same as in Examples 1-6, the mass contents of the additive were as shown in Table 5 below, and the remainder was diethyl carbonate.

[0085] Table 5

[0086] It can be seen from Table 5 that the present application can further improve the interface stability and reduce the volume expansion of the secondary battery by adding additives to the electrolyte and adjusting the mass content of the additives to 0.6% to 8%, preferably 1.1% to 7%.

[0087] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the principles of the present application should be included in the protection scope of the present application.

Claims

1. A secondary battery, characterized in that: It comprises a negative electrode plate and an electrolyte; the negative electrode plate comprises a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector; wherein the negative electrode material layer comprises a first material layer and a second material layer; the first material layer is arranged between the negative electrode current collector and the second material layer; Based on the total mass of the first material layer, the mass content of silicon in the first material layer is x%; based on the total mass of the second material layer, the mass content of silicon in the second material layer is y%; 0≤x≤35, 3.5≤y≤70, and x≤y; The electrolyte comprises a compound of formula I: Formula I Wherein, R1, R2, R3, R4, R5, and R6 are each independently selected from a fluorine atom, a C1-C3 alkyl group, and a fluorine-substituted C1-C3 alkyl group; Based on the total mass of the electrolyte, the mass content of the compound of formula I is A%, 1≤A≤30.

2. The secondary battery according to claim 1, characterized in that: The secondary battery satisfies at least one of the following characteristics: (1)0≤x≤21; (2)10.5≤y≤70。 3. The secondary battery according to claim 1, characterized in that: 2≤A≤20。 4. The secondary battery according to claim 1, characterized in that The thickness of the first material layer is a μm, the thickness of the second material layer is b μm, 15≤a≤100, 5≤b≤70.

5. The secondary battery according to any one of claims 1 to 4, characterized in that: The compound of formula I comprises at least one of the following compounds: Formula I-1, Formula I-2, Formula I-3, Formula I-4, Formula I-5, Formula I-6, Formula I-7, Formula I-8, Formula I-9, Formula I-10, Formula I-11, Formula I-12, Formula I-13, Formula I-14, Formula I-15, Formula I-16, Formula I-17.

6. The secondary battery according to claim 1, characterized in that: The secondary battery comprises a housing and an electrode assembly; The shell is made of steel or aluminum; The volume of the secondary battery is 2 cm 3 ~150 cm 3 .

7. The secondary battery according to claim 1, characterized in that: The secondary battery further comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector; the positive electrode material layer comprises a positive electrode active material; The positive electrode active material is lithium cobalt oxide, and the lithium cobalt oxide includes doping elements; the doping elements include at least one of Mg element, Ti element, Zr element, Nb element, Y element, Cr element, V element, Ge element, Mo element, Sr element, and Al element, and based on the mass of the lithium cobalt oxide, the mass proportion of the doping elements is 0.1%~1%.

8. The secondary battery according to claim 6, characterized in that The volume of the secondary battery is 4 cm 3 ~120cm 3 .

9. The secondary battery according to claim 1, characterized in that: The electrolyte further includes an additive, wherein the additive includes at least one of succinonitrile, adiponitrile, 1,3,6-hexanetrinitrile, 1,2,3-tris(2-cyano)propane, ethylene glycol (bispropionitrile) ether, trans-butene dinitrile, 1,3-propane sultone, and 1,4-butane sultone; Based on the total mass of the electrolyte, the mass content of the additive is B%, and 0.6≤B≤8.

10. An electronic device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Negative pole piece, electrochemical device and electronic device

    CN111261834A

  • Lithium ion battery

    CN115579473A

  • Secondary battery and electronic device

    CN117913217A

  • Electrochemical device and electronic apparatus

    CN118248944A

  • Image decoding apparatus and image encoding apparatus for adaptive quantization and inverse-quantization, and methods thereby

    KR1020240025428A